The De Glind Conference: A Retreat for Young Historians of … Knowledge - Smit, Jorrit (Studium, 2017)
This review attempts to grasp the variety of topics, approaches, and methods presented at the biennial History of Science Phd Conference, held in January 2017 at De Glind, and to embed the Dutch future of history of science in historiographical discussions.